Omni-channel customer management processes in retail: An exploratory study on fulfillment-related options - Johannes Wollenburg; Andreas Holzapfel; Alexander Hübner (Logistics Research, 2019)
Omni-channel retailers systematically connect their sales and communication channels to create a seamless shopping experience. Influencing customers in their channel choices can result in reduced cost to serve customers and increased revenue. To achieve this, comprehensive omni-channel customer management is necessary that also includes fulfillment processes during the customer journey. Operations plays a key role in omni-channel retailing as it is in direct contact with customers and does not end at the store like for bricks-and-mortar retailing. Omni-channel retailing and in particular customer management with fulfillment options is a new topic in practice, and constitutes a new research area. The contribution of this paper lies in building a bridge between sales and operations between online and physical store retailing. We develop propositions that demonstrate how customers can be guided through the channels. We use an exploratory study where data are collected mainly from face-to-face interviews with 25 omnichannel retailers. The objectives of the research include identifying fulfillment-related customer management opportunities via multiple channels used by retailers, assessing the relationships and interdependencies of the customer management methods, and developing propositions for omni-channel customer management. The management options are related to questions such as how customers can collect availability information across channels, how purchase and payment processes are designed, how delivery speed and costs are defined, and which return options are possible. Findings include, among others, that retailers use product availability checks for guiding customers into the store, prioritize certain operational actions, and prevent product returns. If executed in the right way, omnichannel customer management will not only result in differentiation and cross-selling potential for retailers, but also in additional benefit for customers.
Keywords: 650; Omni-Channel Retailing; Customer Management; Exploratory Study; Retail